The barriers and enablers to South African SMEs entering the circular economy - Van Der Poel, Stefan (Graduate School of Business (GSB), 2026)
Purpose - In the linear economy (LE) natural resources are extracted, used to make products and services and are then discarded. This model has two key limitations: firstly, the LE relies on natural resources, which are finite, and the LE generates a significant amount of waste. The proposed solution is switching from a LE to a circular economy (CE), where energy and materials are used repeatedly. Small and medium-sized enterprises (SMEs) are significant contributors to the global economy and are faced with unique challenges. Understanding what factors are most influential in determining the successful transition of South African SMEs from the LE to the CE was the primary objective of the present study. Methodology - The study adopted a quantitative research approach. Through the deployment an online survey, a questionnaire comprised of a series of 5-point Likert scale questions was completed by 62 respondents. The collected data was analysed using descriptive statistics and correlation analysis. Findings - Insufficient government support & funding and a lack of regulatory incentives for CE adoption to be the two most significant barriers facing South African SMEs transition to the circular economy. Conclusion - Until CE business models are viable enough for South African SMEs to transition from the LE to the CE without a reduction in their profitability levels, regulatory incentives will have to be provided by the South African government to make the transition financially viable.